Rungia pectinata (Linn.) Nees: A Review of Phytochemical Analysis and Pharmacological Activities - Forid, Md. Shaekh; Azuri, Muhammad Saupi bin; Wan Ishak, Wan Maznah; Hossain, Md. Sanower (Universitas Muhammadiyah Surakarta, 2024)
Rungia pectinata L. is an herbaceous weed traditionally used for many years for various disease conditions. Nevertheless, these indigenous medical practices are frequently regarded as self-limiting, necessitating a thorough examination of their purported benefits. This review aims to consolidate existing scientific insights and identify domains requiring additional research. The literature was searched using the keyword